Social Activities of Khabarovsk Diocese of Russian Orthodox Church in 1988-2016 - A. V. Drobnitsa; O. V. Seleznyov (Научный диалог)
The question of the formation of community service and charity of the Russian Orthodox Church in the Khabarovsk Territory in the period from 1988 to 2016 in the context of a change in the socio-political system is considered. The research is based on materials from the Khabarovsk Diocesan Administration, the State Archive of the Khabarovsk Territory and the Information and Education Portal of the Khabarovsk Diocese. Particular attention is paid to the processes of the establishment of diocesan bodies in social service and matters of mercy. It analyzes the socio-economic conditions in which the development of the Church’s social ministry in the region took place. The data on the assistance to needy categories of the population are given. It is shown that in the 90s of the twentieth century, the orders of the Moscow Patriarchate were only advisory in nature. The authors of the article believe that in those economic and political conditions this seems justified. It is noted that during this period, the bishops on the ground themselves prioritized the development of church life, in particular with regard to helping those in need. It is emphasized that the development of this direction of church activity began due to the position of His Holiness Patriarch of Moscow and All Russia Kirill (Gundyaev). The novelty of the study is seen in the fact that the charitable activities of the Church during the period under review are practically not affected in publications devoted to the recent history of the Russian Orthodox Church.